FACTORS INFLUENCING THE PERFORMANCE OF - Cosic, Vlado (My University, 2011)
Developments in society, economy and technology have brought about the fast expansion of alternative work arrangements such as telework. In telework people work away from the employer’s central office and use personal computers and/or telecommunications. The main purpose of this study was to determine the factors perceived to influence performance of home based teleworkers in a service company. The company hosting the research provides medical aid insurance and employs home based assessors for the electronic processing of insurance claims. From this research it was found that a number of factors are perceived by teleworkers to influence their performance. The qualitative part of the questionnaire, distributed to the research participants, revealed some factors that were not anticipated from the literature review. This study pointed to elements of psychological contract breach, as this term is used in the literature, and the need for additional skills for teleworkers employed by the company.
MBA - WBS
Keywords: Tele-workers; Home industry